APLIKASI AYAT HUKUM DALAM PENGHAKIMAN KES PEMBUBARAN PERKAHWINAN: KAJIAN DI MAHKAMAH SYARIAH SELANGOR: The Application of the Quranic Legal Verses in the Judgement of the Dissolution of Marriages: A Study at the Selangor Shariah Court - Abdul Ghani, Fadhluzaman; Abdullah, Raihanah (Jurnal Syariah, 2014)
Ayat Hukm or the Quranic Legal Verses is one of the most important components in the implementation of Shariah Judicial Procedure in Malaysia. As to date, Ayat Hukm is fully applied as the strongest or highest source of argument in the Shariah Judicial Procedure, which includes various stages starting from the prosecution, defence and lastly decision stage. In order to preserve its authenticity, the application of Ayat Hukm requires an accurate interpretation on every single Quranic word or term. This method can be found in ‘Ilm Tafsir i.e the knowledge which explains the interpretation of the Quranic verse itself, how the hukm is deduced from such verse as well as the wisdom behind the hukm. Reliance and complete references towards tafsir of al-Qur’an in issuing hukm and enacting the Islamic Family Law will deliver good judgement based on solid interpretation of Ayat Hukm. This study is carried out to identify the position, application and interpretation of Ayat Hukm in Shariah Court in deciding hukm. This study may serve as important references to the committee or any legal institutions and Non-Government Organisation (NGO) specially involved in updating judgement and requirement of technical law in Islamic family matters. Also it is in the interest of Jabatan Kehakiman Syariah Malaysia (JKSM) to explain the strength of authority of hukm in decision making of any dispute settlements. This study focused on the position of Ayat Hukm in the court judgment in relation to ulama’ explanation regarding hukm of dissolution of marriage. An effort was made to collect data from Selangor Shariah Court on cases of talaq, ta’liq, faskh and khul’ and other cases in Selangor as reported in filing case and Jurnal Hukum.